Pengaruh Media Pembelajaran Google Classroom Terhadap Motivasi Belajar Siswa SMK Negeri 2 Purwakarta Mata Pelajaran PAI Pada Masa Covid-19 - Nida Siti Maesaroh; Imam Tabroni; Didin Syaprudin (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2022)
SITIchangesin the learning system using media on the internet. Which has an impact on the learning process, and it is not uncommon for a decrease in student motivation to learn and a decrease in achievement in one school. This studyaims to measure the value of using the Google Classroom learning media and the value of motivation and to determine the effect of the Google Classroom learning media on the learning motivation of students at SMK Negeri 2 Purwakarta for PAI subjects during the Covid-19 period. The approachof this research is quantitative with the correlative method, the research subject is 55 respondents, the data collection technique is using a questionnaire. Based on the results of the questionnaire from 55 students' answers regarding the Google Classroom learning media, that the use of Google Classroom as a learning medium can have a good effect on students' learning motivation with an average value of 81.00%, referring to the percentage and assessment criteria, the figure is in the 63.00 interval. - 81.99 in the good category and students' learning motivation is considered very good with an average value of 82.45% of all questions, referring to the percentage and assessment criteria, the number is in the interval 82.00 - 100.00 with a very good category. The results of hypothesis testing obtained